Evaluasi Sistem Drainase Di Kecamatan Rawalumbu Kota Bekasi - Josua Parmonangan Sinaga; Nico Halomoan (Fakultas Teknik, 2022)
Rawalumbu District has 8 locations of puddle around the area, i.e. Sepanjang Jaya RW 4, Cut Meutia Street, Bumi Bekasi Baru Utara, Pondok Hijau Permai, Pondok Hijau Permai 2, Narogong Jembatan 0 Housing Area, Rawalumbu Housing Area, and across of Trisakti University. There is some reasons why this puddle happened, such as shallow happened in drainage channels, some area doesn’t have drainage channels, wastes stuck in drainage channels, and elevation of some streets lower than drainage channels. The purpose of this research is for evaluates the problem that occur in drainage channels that spread around Rawalumbu District, so puddle doesn’t happen again. This thesis method uses quantitative analysis, when analyzing the existing problems. According to the evaluation result, there is 2.206 channels that overflow and 91 channels that working normally. There is some methods to reduce puddle such as: changing channels that had problems and digging some clay in drainage channels. Sustainable drainage system in this research is planned for controlling the puddle with the help of infiltration wells, there is 34.587 infiltration wells that planned in this research.